2021
DOI: 10.1159/000517925
|View full text |Cite
|
Sign up to set email alerts
|

Do SARS-CoV-2 Infection (COVID-19) and the Medications Administered for Its Treatment Impair Testicular Functions?

Abstract: <b><i>Purpose:</i></b> Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted primarily via respiratory droplets and enters host cells through angiotensin-converting enzyme 2 (ACE-2) receptors. ACE-2 receptors have been identified in many tissues including testes. The aim of the study has been to investigate the long-term effects of SARS-CoV-2 infection (COVID-19) and its relative treatment on male reproductive health. <b><i>Methods:</i></b> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…Further studies about the impact of postponed fertility treatment on sexual health with consideration of different hormone values of infertile patients could be done. A new study found that COVID-19 infection and treatment had no long-term effect on male reproductive health, such as spermatogenesis and serum androgen levels (41). These findings are meaningful for infertile patients, especially for patients who postponed fertility treatment in times of crisis.…”
Section: Discussionmentioning
confidence: 84%
“…Further studies about the impact of postponed fertility treatment on sexual health with consideration of different hormone values of infertile patients could be done. A new study found that COVID-19 infection and treatment had no long-term effect on male reproductive health, such as spermatogenesis and serum androgen levels (41). These findings are meaningful for infertile patients, especially for patients who postponed fertility treatment in times of crisis.…”
Section: Discussionmentioning
confidence: 84%
“…Of 2965 articles identified from the database search, 23 articles were selected for full-text reading. After excluding 2 studies for not providing applicable data on semen quality, 3 articles for no matched control group, and 4 articles for bad quality, we eventually included 14 studies for meta-analysis [21][22][23][24][25][26][27][28][29][30][31][32][33][34], including 8 articles that compared the semen quality between the COVID-19 case group and age-matched control group, and 6 articles comparing patients' sperm parameters before and after COVID-19 infection. The PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis Protocols) flow diagram of the literature screening is presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Almost all COVID-19 patients in the included studies were reported to have recovered from the disease during the semen analysis. The semen analysis in 11 studies was performed following WHO 2010 criteria [21][22][23][24][26][27][28][29], and another 2 studies also adopted the WHO standard, but its version was not informed [25,30]. One study did not explain the guideline on which semen analysis was based, but it is stated that all tests were performed in an EQUAS-certified laboratory [34].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations